COVID-19 initial preparedness and response in Vietnam during the first six months of the pandemic and the lessons for Sendai framework implementation. Issue 1 (9th October 2020) - Linh, Tran Nu Quy; Hanh, Tran Thi Tuyet; Shaw, Rajib
Abstract : Purpose: This paper aims to analyze the current responses applied in Vietnam to the Coronavirus disease (COVID-19) pandemic and link these measures to priority actions highlighted in the Sendai Framework for Disaster Risk Reduction (SFDRR). From there, strengths, limitations and recommendations on applying the SFDRR to build the pandemic resilience in the future are discussed. Design/methodology/approach: The authors synthesize literature on response measures to the COVID-19 pandemic in Vietnam from January to June 2020 and compare to four priority actions of the SFDRR including understanding risk, strengthening governance, investing in risk reduction for resilience and enhancing preparedness for effective response and resilient recovery. Findings: Vietnam has effectively controlled the pandemic with 401 infected cases and no death so far. Well preparation, timely policies' implementation, risk communication and comprehensive approaches are key strategies. These measures are same as the four priority actions in the SFDRR. Originality/value: To the best of the authors' knowledge, this is the first study in Vietnam to link the COVID-19 response and the SFDRR, which can serve as an important example for other countries in responding to the pandemic. Some measures have surpassed SFDRR's guidance, especially preventive responses applied nationwide with strong political will and the community's commitment accompanied by sanctions. Cultural factors such as the habit of using masks to prevent air pollution have contributed to the good observance of wearing mask regulations during the pandemic. However, some areas that need more attention include specific solutions for vulnerable groups, limiting fake news and ensuring patient privacy.